2009
DOI: 10.1007/s00595-008-3850-3
|View full text |Cite
|
Sign up to set email alerts
|

Did ileal knotting trigger labor or did labor cause ileal knotting? Report of a case

Abstract: Ileal knotting is a rare but serious complication of pregnancy, with relatively high maternal and fetal mortality. We report a case of ileal knotting with complications in a pregnant woman without any history of abdominal or pelvic surgery. To our knowledge, there is no other report in the international literature. Thus, the possibility of ileal knotting should be borne in mind when investigating epigastric pain in a pregnant woman without any history of abdominal or pelvic surgery, even after the onset of lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, Alver et al 1 reported a just-married woman, in whom the symptoms of ISK commenced abruptly during the first coitus, which may be connected with the relationship between abnormal body motions and ISK. On the other hand, Ucar et al 11 presented a case, in whom ISK developed following a spontaneous vaginal delivery, and they suggested a cause and effect relation between labour pain and ISK, which might be thought as a kind of abnormal body motions. Similarly, Boukhalit et al 12 reported a case, in whom, ISK was developed just following a delivery and Abebe et al 13 presented another ISK case, who was admitted in hospital 11 hours later a delivery, and they supported the present hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Alver et al 1 reported a just-married woman, in whom the symptoms of ISK commenced abruptly during the first coitus, which may be connected with the relationship between abnormal body motions and ISK. On the other hand, Ucar et al 11 presented a case, in whom ISK developed following a spontaneous vaginal delivery, and they suggested a cause and effect relation between labour pain and ISK, which might be thought as a kind of abnormal body motions. Similarly, Boukhalit et al 12 reported a case, in whom, ISK was developed just following a delivery and Abebe et al 13 presented another ISK case, who was admitted in hospital 11 hours later a delivery, and they supported the present hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 35 patients, (8.4%) had a harvesting activation. Although the relationship between the body motions and SV is not clearly identified in the literature,[ 2 ] some excessive body movements, including harvesting,[ 20 ] first coitus,[ 21 ] and delivery[ 22 ] are reported to be effective in the development of ileosigmoid knotting, which is a complex form of SV. [ 23 ] In our opinion, harvesting and similar cases may initiate SV by forcing the sigmoid colon to rotate around itself.…”
Section: Discussionmentioning
confidence: 99%
“…The management of these clinical entities requires a multidisciplinary approach and the prognoses are still relatively poor with 6%-15% of maternal and 20-30% of fetal mortality in addition to 20%-50% of morbidity in SV, whereas 15%-25% of maternal and 30%-50% of fetal mortality, additionally, 40%-60% of morbidity in ISK. 2 , 10 , 11 , 21 , 23 , 40 - 42 , 53 , 57 , 60, 74 …”
Section: Special Conditionsmentioning
confidence: 99%